Clinical efficacy of acupuncture therapy combined with core muscle exercises in treating patients with chronic nonspecific low back pain: a systematic review and meta-analysis of randomized controlled trials - Li, Xia; Zhai, Guohua; Zhang, Hongkai; Li, Xuefei; Wu, Mingqi; Zhang, Sidi; Cui, Jiawen; Tang, Zhanying; Hu, Zhijun (Frontiers in Medicine, 2024)
Introduction This meta-analysis aimed to determine the clinical efficacy of acupuncture combined with core muscle exercises on pain and functional status in patients with chronic nonspecific low back pain. Methods This study followed the Preferred Reporting Items for Systematic Reviews and meta-analysis criteria for systematic reviews and meta-analyses. Randomized controlled trials published till November 2023 were searched in PubMed, Web of Science, Cochrane, Embase, China National Knowledge Infrastructure, Chinese Biomedical Literature, and Wanfang databases. The search strategy was related to disease type, intervention, and control measures and was structured around the search terms “low back pain,” “acupuncture therapy,” and “exercise.” Two reviewers applied inclusion and exclusion criteria. Sensitivity and fixed effects analyses were performed to determine the primary outcomes. Results We included 11 randomized controlled trials (n = 727) on acupuncture combined with core muscle exercises in patients with chronic nonspecific low back pain. Compared with controls, clinical efficacy was significant, with improvements in pain scores (visual analog pain scale and numerical rating scale) and Oswestry Disability Index in the intervention group. Discussion Acupuncture therapy combined with core muscle exercises improved pain and functional status in patients with chronic nonspecific low back pain, with favorable clinical outcomes compared with single-core muscle training. Multicenter large-sample trials are required to obtain more reliable conclusions.